2008
DOI: 10.1371/journal.pone.0002213
|View full text |Cite
|
Sign up to set email alerts
|

Replicative Senescence of Mesenchymal Stem Cells: A Continuous and Organized Process

Abstract: Mesenchymal stem cells (MSC) comprise a promising tool for cellular therapy. These cells are usually culture expanded prior to their application. However, a precise molecular definition of MSC and the sequel of long-term in vitro culture are yet unknown. In this study, we have addressed the impact of replicative senescence on human MSC preparations. Within 43 to 77 days of cultivation (7 to 12 passages), MSC demonstrated morphological abnormalities, enlargement, attenuated expression of specific surface marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

79
851
4
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 973 publications
(965 citation statements)
references
References 58 publications
79
851
4
10
Order By: Relevance
“…Several independent lines of evidence have indicated a critical role for miRs, as biomarkers of cellular senescence, in both replicative and stress-induced modulation of in vitro cellular senescence (Lafferty-Whyte et al 2009;Poliseno et al 2008;Wagner et al 2008;Li et al 2009Li et al , 2010Olivieri et al 2009). Human umbilical vein endothelial cells (HUVECs) have been extensively used as an in vitro endothelial model representing common functional and morphological features of the in vivo endothelial cells (Unterluggauer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several independent lines of evidence have indicated a critical role for miRs, as biomarkers of cellular senescence, in both replicative and stress-induced modulation of in vitro cellular senescence (Lafferty-Whyte et al 2009;Poliseno et al 2008;Wagner et al 2008;Li et al 2009Li et al , 2010Olivieri et al 2009). Human umbilical vein endothelial cells (HUVECs) have been extensively used as an in vitro endothelial model representing common functional and morphological features of the in vivo endothelial cells (Unterluggauer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When using MSCs for regenerative medicine, it is important to obtain a suffi cient number of cells that maintain pluripotency without compromising MSC senescence. [ 3,4 ] Material systems that mimic the natural niche environment of MSCs may offer an alternative to the use of complex cocktails of soluble factors used in the culture media. Previous studies show that the cell/material interface plays an essential role on MSC function and differentiation, encompassing promising approaches to manipulate differentiation of stem cells ranging from chemistry, [5][6][7] surface modifi cations, [ 8,9 ] topography, [10][11][12] stiffness, [ 13,14 ] and even dynamic material properties such as stress relaxation.…”
mentioning
confidence: 99%
“…The frequency of bipotent clones (with osteo-and chondrogenic potential) decreased with age, and a higher relative frequency of bipotent clones was found in younger donors compared to older donors. Conversely, older donors had a relatively higher frequency of tri-potent clones [51]. Several studies have also assessed tissue regeneration in young mice compared to aged mice.…”
Section: The Aging Microenvironmentmentioning
confidence: 99%
“…However, after a certain number of cell divisions, SCs enter senescence and stop proliferating, showing an enlarged and flattened cell shape [95]. Previous studies have shown that human MSCs exhibit reduced differentiation potentials in vitro and that the replicative senescence of MSC preparations begins with the first passage [51]. Thus, the difficulty in the long-term expansion of MSCs using standard culture systems without the loss of their SC properties suggests that a critical feature of their microenvironment that is necessary for the retention of SC properties is absent in these culture systems.…”
Section: Enhanced Immune Regulationmentioning
confidence: 99%